A liberdade nos caminhos da reconstrução de argumentos entre o direito público e o direito privado - Alves, Manuela Caldas Fontenele (2017)
This academic work focuses on a critical and current approach about the discourse used by the movement for the reconstruction of private law, especially in relation to the role of freedom as the foundation of law. The aim is to verify if the dual study of law allows to understand the legal phenomenon as a whole and if the private autonomy can be configured as a fundamental right to be effective, not merely stated. The arguments outlined are placed in correspondence with the context of transition and questioning of the structures of legal thought of modernity, since the understanding of public and private spaces and of how the juridical phenomenon occurs in these dimensions has profound and quite direct reflexes in many of today's top issues. The methodology adopted for research is to investigate the doctrinal texts pertinent to the subject, prioritizing the national texts and specifically the production closest to the promulgation of the Federal Constitution of 1988 and the Civil Code of 2002.